Metagenomic survey of agricultural water using long read sequencing: Considerations for a successful analysis - Maguire, Meghan; Kase, Julie A.; Brown, Eric W.; Allard, Marc W.; Musser, Steven M.; González-Escalona, Narjol (Frontiers in Environmental Science, 2022)
Leafy greens are responsible for nearly half of the produce-related Shiga toxin-producing Escherichia coli (STEC) outbreaks in the United States and recent investigations have implicated agricultural water as a potential source. Current FDA detection protocols require extensive analysis time. We aimed to use Oxford Nanopore rapid sequencing kits for an in-field determination of agricultural water microbiome and possible detection and characterization of STECs strain(s) in these samples. We tested the performance of the nanopore rapid sequencing kit (RAD004) for fast microbiome determination using the well characterized ZymoBIOMICS mock microbial community and the number of reads for each identified species was present in the expected proportion. Rapid sequencing kit (LRK001 and RAD004) library preparation of DNA extracted from agricultural water resulted in poor nanopore sequencing reactions, with low output (0.3–1.7 M reads), a high proportion of failed reads (50–60%), and highly sheared DNA before and after a magnetic bead clean up. To improve performance, we prepared a DNA library with the ligation kit (LSK109), which includes multiple cleaning steps, reducing inherent inhibitors and producing a better outcome (2.2 M reads, 15% failed reads). No definitive presence of STEC could be confirmed in any of the sites. Approximately 100 reads from each site (0.02% of total reads) were identified as Escherichia coli, but the specific strain or their virulence genes could not be detected. Sites 9, 10, and 12 were found to be positive for STEC presence by microbiological techniques after enrichment. The rapid sequencing kits can be appropriate for genus or species level microbial identification, but we recommend the use of the ligation kit for increased sequencing depth and removal of contaminants in agricultural water. However, we were not able to identify any STEC strains in these nanopore microbiome samples, due to low initial concentrations. The results from this pilot study provide preliminary evidence that MinION sequencing of agricultural water using the ligation kit has the potential to be used for rapid microbiome determination in the field with optimal results for water quality surveillance.